SICS – a cost effective alternative to phacoemulsification for developing countries in Nepal - Nowakowski, Rafał (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Millions of people worldwide are blind from mature cataracts. The developing countries cannot afford expensive modern technologies to treat these cases. A cost effective, fast, machine independent procedure is necessary. The purpose of this study is to describe such a technique, little known in Poland – manual small incision cataract surgery (SICS), where the whole nucleus is removed through a self-sealing sclero-corneal tunnel. Within the last several years SICS has become the main way of cataract removal in underserved populations of Asia, with Nepal as an example. Thus, the developing countries have developed a cost effective alternative to phacoemulsification with a very good clinical outcome.